PENCAPAIAN BREAK EVEN POINT (BEP) PETERNAKAN AYAM PETELUR YANG MENGGUNAKAN PAKAN PRODUK PABRIK SKALA KECIL (Studi Kasus Pada Peternakan Ayam Ras Petelur di Kabupaten Sidrap Sul-Sel) - Irmasusanti Subaidah (MADURANCH: Jurnal Ilmu Peternakan, 2012)
This aims of the study was to analyze the business economically layer poultry farms medium scale. The study was conducted with case studies and data were analyzed using analysis of the economic aspects of revenue, R/C ratio, Profit Margin (PM), and Break Event Point (BEP). The results showed that the layer farm business medium scale economically profitable.